Phytochemical Screening, Cytotoxic Activity, Antibacterial Assay and Proximate Analysis of Ulva Intestinalis Algae from the Bay of Bengal, Bangladesh (Bioresearch Communications, 2023)
Seaweed is widely popular across the globe for its nutritional and biological properties. After delimiting the maritime boundary on Bangladesh, research on seaweeds is gaining momentum. Ulva intestinalis is one of the seaweeds found in the St. Martin’s Island of Bangladesh, and the present study investigated the presence of potentially bioactive compounds through phytochemical screening and proximate analysis of Ulva intestinalis along with cytotoxicity test and antibacterial activity. Phytochemical screening of ethanolic extract of Ulva revealed the presence of alkaloids, steroids, flavonoids and coumarins. The cytotoxicity and antibacterial activity was also found to be significant by the algal extract. From the quantitative test of nutrients, it demonstrated that the seaweed contains 15.41% of protein, 51.79% of carbohydrate, 1.21% of fat, 3.74% of fiber, 18.81% ash, and 12.78% moisture. Additionally, the presence of vitamin B12 was promising (1300 μg/100 g). Interestingly, heavy metals were not detected in Ulva intestinalis whereas other micronutrients were present. Comparatively, the higher ZOI were showed in Klebsiella pneumoniae, Salmonella sp and E.coli than micrococcus sp which indicates higher antibacterial activity of the species. The result of the brine shrimp lethality test, greater cytotoxicity of crude algal extract showed a significant LC50 value with higher concentrations. As a result, it is plausible that Ulva intestinalis, from the Bay of Bengal, has the potential antibacterial and cytotoxic activities and might also serve as a source of new bioactive compounds. Moreover, further research is needed to perform for validation of the seaweed to introduce its medicinal activity or nutritional supplement potentiality in industrial scale.Bioresearch Commu. 10(1): 1424-1431, 2024 (January)